Mangifera indica L. Leaves Extract Induced Intrinsic Apoptotic Pathway in MCF-7 Cells by Decreasing Bcl-2 Expression and Inducing Bax Expression - Fitriasih Fitriasih; Siti Mega Komariyah; Ferry Sandra; Nenni Pratiwi; Devi Nisa Hidayati (Indonesian Society for Cancer Chemoprevention, 2019)
Extract of Mangifera indica L. has been investigated to have cytotoxic activity against MCF-7 cells. Current research was conducted to determine the cytotoxic activity of methanol extract of M. indica leaves (MEML) on MCF-7 breast cancer cells and to investigate on the MEML's effect on Bcl-2 and Bax expressions. M. indica leaves were extracted using soxhletation with methanol. The cytotoxic test was perfomed using MTT assay with various MEML concentrations: 15.625, 31.25, 62.5, 125, 250 and 1000 μg/mL. Meanwhile, Bax and Bcl-2 expressions of MCF-7 breast cancer cells were detected with immunocytochemical staining after treatment of MEML with concentrations of ¼ IC50, ½ IC50 and IC50. The results showed that IC50 of cytotoxic activity was 308.12 µg/mL. MEML could influence Bax and Bcl-2 protein expressions. After treatment of MEML, Bcl-2 expression was decreased while Bax expression was increased.Keywords : Mangifera indica L., Cytotoxic, Bax, Bcl-2, MCF-7